Acid-Base Properties of 2-Morpholinoethanesulfonic Acid (MES), Complexation Reaction of CuII-MES, and Interaction of Hydrous Manganese Oxide Surface with CuII in MES Buffer - Antoine Balikungeri (CHIMIA)
The acidity constants of 2-morpholinoethanesulfonic acid (MES) have been determined at various ionic strengths; pKa1 = 1.99 and pKa2 = 6.21 at ionic strength I = 0.1 M. The conditional stability constant of CuII-MES complex has been measured by means of a CuII-ion selective electrode: lg cKCu-MES = 1.39 ± 0.07 at pH = 5.57. Furthermore the interaction between CuII and hydrous manganese oxide surface in MES buffer was studied by differential pulse polarography. Conditional stability constants for CuII-MnOx complex (SCu) at three pH values were calculated by two methods: van den Berg-Ružić method as well as the Scatchard plot yield corresponding values for lg cKSCu. Both methods indicated the presence of one class of equivalent binding sites. The results of this investigation corroborate that MES is a suitable buffer for studying metal-MnOx interactions.